Regulation of B-cell development and tolerance by different members of the miR-17∼92 family microRNAs - Maoyi Lai (Nature Portfolio, 2016)
MicroRNA cluster 17∼92 plays a critical role in B-cell differentiation. Here the authors show that miR-19 regulates B-cell tolerance via suppressing the expression of PTEN, whereas miR- 17 is essential for early B-cell development independently of Pten, Phlpp2, or Bim.